Taurocholate Induces Biliary Differentiation of Liver Progenitor Cells Causing Hepatic Stellate Cell Chemotaxis in the Ductular Reaction: Role in Pediatric Cystic Fibrosis Liver Disease - Pozniak, K.; Pearen, M.; Pereira, T.; Kramer, C.; Kalita-De Croft, P.; Nawaratna, S.; Fernandez-Rojo, M.; Gobert, G.; Tirnitz-Parker, Nina; Olynyk, John; Shepherd, R.; Lewindon, P.; et al. (Elsevier Inc., 2017)
Cystic fibrosis liver disease (CFLD) in children causes progressive fibrosis leading to biliary cirrhosis; however, its cause(s) and early pathogenesis are unclear. We hypothesized that a bile acid–induced ductular reaction (DR) drives fibrogenesis. The DR was evaluated by cytokeratin-7 immunohistochemistry in liver biopsies, staged for fibrosis, from 60 children with CFLD, and it demonstrated that the DR was significantly correlated with hepatic fibrosis stage and biliary taurocholate levels. To examine the mechanisms involved in DR induction, liver progenitor cells (LPCs) were treated with taurocholate, and key events in DR evolution were assessed: LPC proliferation, LPC biliary differentiation, and hepatic stellate cell (HSC) chemotaxis. Taurocholate induced a time-dependent increase in LPC proliferation and expression of genes associated with cholangiocyte differentiation (cytokeratin 19, connexin 43, integrin ß4, and ?-glutamyltranspeptidase), whereas the hepatocyte specification marker HNF4a was suppressed. Functional cholangiocyte differentiation was demonstrated via increased acetylated a-tubulin and SOX9 proteins, the number of primary cilia + LPCs, and increased active ?-glutamyltranspeptidase enzyme secretion. Taurocholate induced LPCs to release MCP-1, MIP1a, and RANTES into conditioned medium causing HSC chemotaxis, which was inhibited by anti-MIP1a. Immunofluorescence confirmed chemokine expression localized to CK7 + DR and LPCs in CFLD liver biopsies. This study suggests that taurocholate is involved in initiating functional LPC biliary differentiation and the development of the DR, with subsequent induction of chemokines that drive HSC recruitment in CFLD.